Effect of ureteric stone location on the success rate of ureteroscopic Holmium laser lithotripsy - Ahmed, Mohamed F.; Othman, Asaad I.; Mohammad, Uday H. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Ureteral stone can cause obstructive uropathy and subsequent deterioration of renal function. There are four treatment options for ureteral calculi: lithotripsy, ureteroscopy, laparoscopic ureterolithotomy, and open stone surgery. Holmium YAG laser is an excellent intracorporial lithotripter for all kinds of stones. Accordingly, there is steady increase in number of ureteroscopic laser lithotripsy operations in the managmant of Ureteral stone.Objectives: this study was designed to demonstrate the effect of ureteric stone location on the success rate of ureteroscopic Holmium laser lithotripsy in the management of ureteric stones.Patients and Methods: Ninety middle-aged patients of either sex (35.9 ± 10.8 years) with ureteric stone (9.5 ± 3 mm) were treated with semiregid ureteroscopy using Holmuim: YAG laser as an intracorporial lithotripter. In 32 patients (35%) the stone were located in the lower ureter, 22 patients (24%) in middle ureter and in 36 patients (40%) in the upper ureter. Then all the patients were followed up on day 1 and 4 weeks for clearance of stone by plain abdominal radiography and abdominal ultrasonography.Results: the stone free rates 4 weeks after the treatment were 66% for upper, 75 % for middle and 87.5% for lower ureteric stones.  In 12 patients (13%)cannot be possible to  reach the stone, six patients (6.6 %) had proximal stone migration and treated later on by extracorporeal lithotripsy after double-J stent placement. Ureteral perforation occurred in 7 patients (7.7%), all managed by double-J stent placement except 1patient needed an open surgical treatment..Conclusion: YAG laser lithotripsy is efficacious modality of treatment for ureteric stones especially in lower ureter and it is a safe and technically feasible and in early experience, it is preferred to start with more distal stones.